Transcriptomic analysis to infer key molecular players involved during host response to NDV challenge in Gallus gallus (Leghorn & Fayoumi) - Venkata Krishna Vanamamalai (Nature Portfolio, 2021)
Abstract Long non-coding RNAs (lncRNAs) are the transcripts of length longer than 200 nucleotides. They are involved in the regulation of various biological activities. Leghorn and Fayoumi breeds of Gallus gallus were known to be having differential resistance against Newcastle Disease Virus (NDV) infection. Differentially expressed genes which were thought to be involved in this pattern of resistance were already studied. Here we report the analysis of the transcriptomic data of Harderian gland of Gallus gallus for studying the lncRNAs involved in regulation of these genes. Using bioinformatics approaches, a total of 37,411 lncRNAs were extracted and 359 lncRNAs were differentially expressing. Functional annotation using co-expression analysis revealed the involvement of lncRNAs in the regulation of various pathways. We also identified 1232 quantitative trait loci (QTLs) associated with the genes interacting with lncRNA. Additionally, we identified the role of lncRNAs as putative micro RNA precursors, and the interaction of differentially expressed Genes with transcription factors and micro RNAs. Our study revealed the role of lncRNAs during host response against NDV infection which would facilitate future experiments in unravelling regulatory mechanisms of development in the genetic improvement of the susceptible breeds of Gallus gallus.